(3OjhGf GdMGLQjs - (3MSGe GdOjf Hf YjSi Hf SfLQ Hf HgQGe Hf LHQjd GdEQHdj GdeYQha H` GdMGLQi,J (B639 (3g` s ((3eMSf Hf Ydj Hf eMeO Hf GdMSjf s)
(3ChdgG (B:s
(3eG ddOehY JSjd Sjd GdhGOj CMOkG HQcH GdYGeQjI MGOj s
(3BNQgG (B:s
(3LYdJ aOGg ef eYOd heeQV hoeMJLH Hjf GdCSfI eYQV haj GdbdH ef EYQGVg Ohf MLHg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGdKs
(3GfXQgG eY GdMSf GdUQjM ddUaOjs
(3fSNI QGHYIs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B25s
Keywords: (3GdCOHs